1976
DOI: 10.1111/j.1471-4159.1976.tb12284.x
|View full text |Cite
|
Sign up to set email alerts
|

METABOLIC RELATIONSHIPS BETWEEN MYELIN SUBFRACTIONS: ENTRY OF PROTEINS 1

Abstract: Abstract— Partially purified myelin from brains of 17‐day‐old rats was separated into 4 subfractions on a discontinuous sucrose gradient by virtue of heterogeneity in density and particle size. The protein composition of each subfraction was determined by densitometry following separation of proteins on polyacrylamide gels in buffers containing sodium dodecyl sulphate. The major proteins studied included two basic proteins, proteolipid protein, the major high molecular weight protein (W) and a group of high mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
1

Year Published

1977
1977
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 21 publications
6
22
1
Order By: Relevance
“…For example, ing similarities, are nevertheless distinct. Our findings there is evidence that MBP is synthesized close to the have confirmed previous observations obtained from immyelin compartment (Benjamins et al, 1976; Colman et munocytochemical studies; they have shed new light on al., 1982; Pereyra et al, 1983). This accords with the the relationship between the plasma membrane and finding that B3.f OLG synthesize little MBP (Yim et al, myelin; and they have also sharpened old controversies 1986) just as mature oligodendrocytes in situ do not or opened new ones.…”
Section: Discussionsupporting
confidence: 94%
“…For example, ing similarities, are nevertheless distinct. Our findings there is evidence that MBP is synthesized close to the have confirmed previous observations obtained from immyelin compartment (Benjamins et al, 1976; Colman et munocytochemical studies; they have shed new light on al., 1982; Pereyra et al, 1983). This accords with the the relationship between the plasma membrane and finding that B3.f OLG synthesize little MBP (Yim et al, myelin; and they have also sharpened old controversies 1986) just as mature oligodendrocytes in situ do not or opened new ones.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, it was concluded that the relative amounts ofBP and PLP are not necessarily constant in different fibers even in the mature myelin membrane. This conclusion is consistent with previous biochemical measurements that have shown a difference in the ratio ofBP and PLP in myelin subfractions separated on sucrose density gradients (13)(14)(15) and in myelin prepared from different brain regions (15)(16)(17). Other myelin-specific proteins might be expected to show similar heterogeneity in concentration.…”
supporting
confidence: 93%
“…At short intervals after injection of radioactive precursor, the specific radioactivity of a given component is higher in fractions at the bottom of the gradient than in those at the top, suggesting that membranes in the lower fractions may be precursors of those above. This relationship has been demonstrated for sulfatide , total protein (Agrawal et al, 1974), phospholipids (Benjamins et al, 1976c), and the BP and PLP (Benjamins et al, 1976b). 3.…”
Section: Studies With Subcellular Fractionsmentioning
confidence: 68%
“…This fractionation has been done by centrifugation either on discontinuous sucrose density gradients (D. H. Adams and Fox, 1969;Mehl, 1972;A. W. Zimmerman et al, 1975;Fujimoto et al, 1976;Cammer et al, 1977;Benjamins et al, 1976) or on continuous gradients in a zonal rotor (Bourre et al, 1980;Matthieu et al, 1979a;Waehneldt, 1978a,b). By the latter technique, myelin preparations from the adult central nervous system (CNS) are distributed along a bell-shaped curve covering a range of sucrose concentrations of 0.5-0.9 M and centered on 0.67 M sucrose (d = 1.08) (Waehneldt, 1978a).…”
Section: Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation